FIRST AID EDUCATION DURING INJURY IN CHILDREN WITH RICE METHOD AT SEKOLAH INDONESIA SINGAPURA (SIS) - Sugiantoro, Natasya Putri; Huda, Mochammad Maftuchul; Setyorini, Dwi; Azizah, Siti Nur (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2024)
First Aid is an aid for emergency treatment of victims before help is provided by medical personnel. Injuries can occur anywhere, the location of injuries often occurs especially in the home and school environment. School-age children are a group that is vulnerable to injury, especially when entering celementary school. Injuries can become an emergency case and cause serious injuries and even death if not handled properly. To prevent injuries in children from getting worse, one of the methods that can be used to treat is the RICE (Rest, Ice, Compression, Elevation) method, which can first rest the injured part, apply an ice pack to reduce swelling, bandage the injured skin and elevate the injured area above the height of the heart area. First Aid community service with the RICE method at Sekolah Indonesia Singapura (SIS) is a positive activity that aims to increase children's knowledge and ability to perform first aid when injured or when children know other people are injured. The method used is counseling about first aid for injuries using the RICE method, demonstrating and distributing leaflets. The results of the analysis of children's ability to understand first aid material when injured with the RICE method before and after education is 30 (with an average pre test score of 70 and post test 100).  The increase in participants' knowledge proves that with this counseling participants become more aware of what is related to first aid during injuries that can be treated with the RICE method to prevent more severe injuries. Keywords; First Aid, Emergency, RICE, Children